Gender differences in Information retrieval skills and use of electronic resources among information professionals in South-western Nigeria (2013)
The study investigated the gender differences in information retrieval skills and use of electronic resources based on a sample of 175 information Professionals surveyed in academic libraries in South - Western Nigeria, The sample was selected from a population of 250 information Professionals using a simple random sampling technique. Data for the study were collected by using structured questionnaire. Descriptive statistics of frequency counts, simple percentages and inferential statistics of t-test and correlation analysis were used for data analysis. The findings did not reveal that gender differences exist between male and female information Professionals on the basis of acquisition of information retrieval skills. Similarly, there was no statistically significant difference in respondents’ _se of electronic resources. However, the study showed that male Professionals revealed a slightly higher mean score on their use of electronic resources. The paper discussed implications of these results on staff's development and capacity building in library and information centres with respect to ICT skills acquisition especially in a gender -sensitive environment.